Sclerotherapy in tumescent anesthesia of reticular veins and telangiectasias - Ramelet, Anne-Sylvie (2012)
Background Some leg telangiectasias may be refractory to treatment, including sclerotherapy and lasers. Objective To describe the innovative Sclerotherapy in Tumescent Anesthesia of Reticular veins and Telangiectasias (START) approach to achieving good results in such patients, which also proves effective in treating reticular veins. Method Because compression enhances the rate of success of sclerotherapy of C1 veins (telangiectasias and reticular), Ringer solution (with or without lidocaine-epinephrine) was injected subcutaneously before, during, or immediately after sclerotherapy of therapy-refractory C1 veins. This tumescence ensures an intratissular compression of the injected vessels for at least 1 hour. Results In the last 6 years, we have treated more than 300 patients. Telangiectasias that had resisted several previous treatments faded or disappeared in the majority of the cases treated, but the rate of complications (pigmentation, necrosis of small areas, and tiny scars) was higher than with usual sclerotherapy. Conclusion Developed after observing the good results achieved by perioperative sclerotherapy of telangiectasias during ambulatory phlebectomy, the START technique is an effective and economic treatment of therapy-resistant telangiectasias, although because the rate of complications is higher than with usual sclerotherapy of C1 veins, it should be performed only by experienced phlebologists and only on therapy-refractory vessels. © 2012 by the American Society for Dermatologic Surgery, Inc. Published by Wiley Periodicals, Inc.